PHONETIC CHARACTERISTICS OF DIFFERENT SPEECH STYLES IN ENGLISH COMMUNICATION - Jabbarova Sevinch Jasurovna; Fayzulloyeva Zilola Zafarovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: In English, speakers may use different phonetic features such as stress, intonation, rhythm, and sound reduction when they speak in formal or informal environments. Understanding these phonetic changes helps explain how speech styles function in real communication. The aim of this article is to examine the phonetic characteristics of different speech styles in English communication. The study focuses on how pronunciation patterns vary between formal and conversational speech. In order to achieve this goal, the research analyzes linguistic literature related to English phonetics and observes common pronunciation patterns in different speech situations. The results show that speech style significantly influences phonetic realization.